(untitled) (Jurnal Adabiya, 2020)
Managing knowledge is a crucial aspect for technological industries, such as telecommunication companies. The companies can gain benefit from employee’s knowledge to improve company services as well as to develop advanced products. In fact, managing knowledge is not easy to do considering organization’s cul- ture. The aim of this paper is to analyze the challenges to apply knowledge managementsystem in a multina- tionaltelecommunicationcompany. Thetypeofthisresearchisstudycase.Datawerecollected byinterviewing key persons and it was analyzed by using Miles and Huber Man model. The result shows that capturing tacit knowledge and developing collaborative environment become challenges for Ericsson to manage knowledge. Mostly,staffs preferto keep theirtacit knowledgeratherthantosharethatknowledge.Thisstudyrecommends todevelopcollaborativeenvironmentbybuildingtrustamong staffsthroughgroupdiscussion.